PENERAPAN MODEL PROJECT BASED LEARNING DALAM MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA PADA TEMA 8 LINGKUNGAN SAHABAT KITA DI KELAS V SD NEGERI 173416 POLLUNG TAHUN PEMBELAJARAN 2022/2023 - Eliezer Siringoringo; Dewi Anzelina; Ester Julianda Simarmata; Juliana Juliana; Sahut Mahulae (JURNAL HANDAYANI PGSD FIP UNIMED, 2023)
This Classroom Action Research (PTK) aims to determine the increase in students' critical thinking skills by using the Project Based Learning model on the theme 8 Our Friend's Environment in class V SD Negeri 173416 Pollung 2022/2023 Academic Year. This research was conducted in 2 cycles. It can be seen from the results of the research carried out in the pretest (preliminary test) students obtained a complete score of 7 students (28%) while 18 students (72%) did not complete, with an average student learning outcome of 57. At the post test stage cycle I increased to 12 students who completed (48%) and students who did not complete as many as 13 students (52%), with an average student learning outcome of 69. In the post-test stage of cycle II there was an increase to 22 students who completed (88%) ) and 3 students (12%) did not complete, with an average student learning outcome of 86. From the results obtained it can be concluded that by using the Project Based Learning model on the theme 8 Our Friendly Environment in class V SD Negeri 173416 Pollung in the 2022/2023 Academic Year.Keyword: Critical Thinking Skills, Project Based Learning, Cycle Penelitian Tindakan Kelas (PTK) ini bertujuan untuk mengetahui peningkatan kemampuan berpikir kritis siswa dengan menggunakan model Project Based Learning pada tema 8 Lingkungan Sahabat Kita di kelas V SD Negeri 173416 Pollung Tahun Pembelajaran 2022/2023. Penelitian ini dilaksanakan dengan 2 siklus. Dapat dilihat melalui perolehan penelitian yang diselenggarakan ketika pratest (tes awal) siswa mendapati nilai ketuntasan sejumlah 7 atau (28%) melankan yang tak tuntas sejumlah 18 (72%), pada kisaran perolehan pembelajaran 57. Dalam post test siklus I menaik 12 siswa yang tuntas (48%) serta yang tak tuntas 13 (52%), pada kisaran perolehan pembelajaran 69. Ketika post test siklus II ada kenaikan 22 yang tuntas (88%) serta yang tak tuntas sejumlah 3 (12%), pada kisaran perolehan pembelajaran 86. Dari hasil yang diperoleh dapat disimpulkan bahwa dengan menggunakan model Project Based Learning pada tema 8 Lingkungan Sahabat Kita di kelas V SD Negeri 173416 Pollung Tahun Pembelajaran 2022/2023.Kata Kunci: Kemampuan Berpikir Kritis, Project Based Learning, Siklus